The relationship between individual factors and knowledge sharing among employees at Karangkraf administrative department, Shah Alam/ Ahmad Naim Ahmad Nadzari and Raja Abdullah Yaacob - Ahmad Nadzari, Ahmad Naim; Yaacob, Raja Abdullah (Faculty of Information Management, Universiti Teknologi MARA, 2014)
Individual factors have been known of their significant impact on knowledge sharing in organizations. It is the aim of this study to examine the relationship between individual factors and knowledge sharing among employees at the Karangkraf Administrative Department, Shah Alam. Questionnaires were used to get information from the student such as attitudes and behavior, motivation and trust from the individual factors. The total respondents are 44 students were selected randomly. This study uses Descriptive Statistic, Pearson Correlation and Cronbach's Alpha in order to analyze the data gathered by using Statistical Package for Social Sciences (SPSS).